Dynamic damping of dislocations with phonons in Kbr single crystals - Petchenko, A.M.; Petchenko, G.A. (Functional Materials, 2006)
The damped dislocation resonance in KBr crystals has been studied using the pulse echo method in the frequency range 7.5 to 217.5 MHz and temperature range 77-300 K. In samples with per-deformation 0.23 and 0.5% the difference in dislocation density has been found to do not influence the temperature course of the damping constant B.